KOMBINASI PRENATAL YOGA DENGAN BIRTH BALL EFEKTIF TERHADAP LAMA PERSALINAN KALA I FASE AKTIF - Suryaningsih, Ning; Mardiana Ahmad; Nontji, Werna; Syam, Yuliana; Usman, Andi Nilawati; Arsyad, M.Aryadi (Media Penelitian dan Pengembangan Kesehatan, 2024)
Labor problems that often occur are the inability of the uterus to contract effectively, but by doing prenatal yoga and using a birth ball, the uterine muscles can be more relaxed so that the labor process becomes smoother. The study aimed to analyze the effect of prenatal yoga, birth ball and prenatal yoga with birth ball on the duration of active phase I labor. Quasi-experimental method, post-test comparative group design. Sampling using purposive sampling technique. The sample of this study amounted to 60 respondents, divided into three groups. Data were collected with observation sheets and analyzed using the Kruskal Wallis test to see the effect of independent variables, namely prenatal yoga, birth ball, and prenatal yoga with birth ball on the dependent variable of the duration of active phase I labor. The findings showed, the prenatal yoga group in the active phase I was normal 18 (90%) respondents, p-value 0.002, mean rank 90.28. Birth ball group of active phase I normal labor 18 (90%) respondents, p-value 0.000, mean rank 90.50. Prenatal yoga group with birth ball active phase I normal labor 16 (80%) respondents, p-value 0.005, mean rank 87.70.The results of the analysis of the three groups simultaneously obtained prenatal yoga r=81.916, birth ball r=93.412, prenatal yoga with birth ball r=87.714. There is difference between the three groups with p value = 0.001. In conclusion, both in groups and simultaneously, the three groups, have a significant effect on the duration of active phase I labor.